The Analysis of the Pragmatic Failures in Body Language Based upon Geert Hofstede’s Cultural Dimensions - Jing, Xi; Ping, Liu; Yanjiao, Li; Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
Pragmatic Failures in Non-verbal takes majority as for the sources of failures in cross-cultural communication, mainly including the pragmatic failures in body language, paralanguage, object Language as well as the environmental language. Body Language is a kind of non-verbal Lingua Franca which is most frequently used, widest various and deepest linked to non-verbal communications. Therefore, based upon Geert Hofstede’s Cultural Dimensions, this article was SPSS to analyze the collected data and conduct typical case analysis towards the Pragmatic Failures in body language in cross-cultural communication, aiming at enhancing the consensus of the majority of foreign language learners as for cross-cultural awareness, thereby to significantly reduce the frequencies of the failure in cross-cultural communication. The various connotation for all kinds of typical Body Language in different cultural background, and then to reduce the Pragmatic Failures in cross-cultural communication farthest, so that all kinds of cross-cultural communications or activities can be carried-out smoothly